2017
DOI: 10.1109/toh.2017.2671376
|View full text |Cite
|
Sign up to set email alerts
|

Friction Reduction through Ultrasonic Vibration Part 2: Experimental Evaluation of Intermittent Contact and Squeeze Film Levitation

Abstract: In part 1 of the current study of haptic displays, a finite element (FE) model of a finger exploring a plate vibrating out-of-plane at ultrasonic frequencies was developed as well as a spring-frictional slider model. It was concluded that the reduction in friction induced by the vibrations could be ascribed to ratchet mechanism as a result of intermittent contact. The relative reduction in friction calculated using the FE model could be superimposed onto an exponential function of a dimensionless group defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 11 publications
(30 reference statements)
3
35
0
Order By: Relevance
“…The illusion of a ridge (33) may be created by rapidly increasing friction during the exploration by a finger as a result of decreasing the amplitude of vibration or increasing the electrostatic field (3). The strength and stability of this effect are dependent on the contrast in friction that can be induced, which has critical implications for power requirements (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The illusion of a ridge (33) may be created by rapidly increasing friction during the exploration by a finger as a result of decreasing the amplitude of vibration or increasing the electrostatic field (3). The strength and stability of this effect are dependent on the contrast in friction that can be induced, which has critical implications for power requirements (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Two different mechanisms have been suggested to explain the cause of friction reduction in ultrasonic tactile displays; Watanabe et al [2] proposed that the friction reduction is due to the formation of a squeezed film of air between finger and the surface. Alternatively, it has been suggested that, when a surface vibrates at an ultrasonic frequency, an intermittent mechanical contact develops between finger and the surface such that the finger bounces on the surface while sliding [3]- [5]. A recent study conducted by Wiertlewski et al [6] using a stroboscope revealed that both mechanisms indeed contribute to the friction reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in order to modulate friction on a touch surface properly, it is important to understand our tactile perception of change in friction and the contact mechanics behind it. Although, the earlier studies have investigated the contact mechanics of friction [5], [10]- [17] and our perceptual ability to discriminate two different surfaces based on friction [18]- [20], the number of studies investigating the intermittent contact mechanics during a change in friction on a touch surface is very limited [21]- [24]. Furthermore, the factors affecting our tactile perception of this change have not been investigated in depth yet [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such technique is electrovibration, which creates an electrostatic attraction between the finger and the actuated surface and increases the finger-surface friction [1], [2]. Another technique, ultrasonic lubrication [3] is able to reduce the finger-surface friction by generating a squeeze film effect and an intermittent contact with the surface [4]- [6] either through a stationary wave on the whole surface or through evanescent waves within a precise location [7]. These technologies have very different means of action but they nevertheless induce a change in the dynamic friction between the finger and the tactile plate, which is similarly perceived [8].…”
Section: Introductionmentioning
confidence: 99%